IMPLEMENTATION OF ARABIC LEARNING IN JUNIOR HIGH SCHOOL - Zulheddi Zulheddi; Sefira Wardani (Tadrib: Jurnal Pendidikan Agama Islam, 2022)
This study aims to analyze: 1) Learning Arabic in Galih Agung Private Junior High School, 2) Implementation of learning Arabic in Galih Agung Private Junior High School. 3) The results of the implementation of Arabic learning in Galih Agung Private Junior High School. This research is a qualitative descriptive study. Descriptive research was designed to obtain information about the symptoms of the status when the study was conducted. The sources of primary data in this study are data obtained from events in the study or existing witnesses, such as interviews with principals, teachers and related students. While the sources of data in this study are documents related to learning Arabic and outside the specified informants. The results of the study show that: 1) Arabic learning in Galih Agung Private Junior High School includes: curriculum, objectives, methods and evaluation system for Arabic learning. The pesantren curriculum (Arabic language material) applied to Galih Agung Private Junior High School students includes: Arabic, Al-khat, Tauhid, Mahfuzat, Nahwu, Sorof, Tafsir, Muthala'ah, Fiqh, Faraidh, Insha', and Imla'. 2) The implementation of Arabic learning at Galih Agung Private Junior High School is carried out every day, with different Arabic subjects. 3) The results of the implementation of Arabic learning there are few students who are not fluent in Arabic because these students come from public elementary schools (SD) not from Madrasah Ibtidaiyah (MI) or Integrated Islamic Elementary Schools (SDIT).